New iterative method for solving chemistry problem - Ghosh, Indranil; Chowdhury, Md. Sazzad Hossien; Mt Aznam, Suazlan; Mawa, Shukranul (National University of Uzbekistan, 2020)
The chemical kinetics model or chemistry problem is extremely well known in nonlinear science. In this paper, we implement a semi analytical technique, the New Iterative Method (NIM), for solving chemical kinetics systems which appear in the form of nonlinear ordinary di˙erential equations. To examine the reliability and e˙ectiveness of the technique, first we solved the selected system by the fourth-order Runge-Kutta method (RK4) and then by New Iterative Method (NIM). Numerical outcomes show good agreement of the proposed technique in terms of precision compare to conventional fourth-order Runge-Kutta method (RK4). It is notable that this procedure requires less computational exertion and provides fast approximate solutions without any transformation, linearization and discretization. Consequently, it can be predicted that the NIM is an eÿcient approach in finding approximate numerical solutions for a wide range of initial value problems.